Developing tools for learning oriented assessment of interactional competence: Bridging theory and practice. (April 2020) - May, Lyn; Nakatsuhara, Fumiyo; Lam, Daniel; Galaczi, Evelina
In this paper we report on a project in which we developed tools to support the classroom assessment of learners' interactional competence (IC) and provided learning oriented feedback in the context of preparation for a high-stakes face-to-face speaking test. Six trained examiners provided stimulated verbal reports ( n = 72) on 12 paired interactions, focusing on interactional features of candidates' performance. We thematically analysed the verbal reports to inform a draft checklist and materials, which were then trialled by four experienced teachers. Informed by both data sources, the final product comprised the following: (a) a detailed IC checklist with nine main categories and over 50 sub-categories, an accompanying detailed description of each area and feedback to learners, which teachers can adapt to suit their teaching and testing contexts; and (b) a concise IC checklist with four categories and bite-sized feedback for real-time classroom assessment. Interactional competence, a key aspect of face-to-face communication, is under-researched and under-explored in second/foreign language teaching, learning, and assessment contexts. This in-depth treatment of it, therefore, stands to contribute to learning contexts through raising teachers' and learners' awareness of micro-level features of the construct, and to assessment contexts through developing a more comprehensive understanding of the construct.